Тенденції формування системи контролінгу на підприємствах машинобудування України - Другова, Олена Сергіївна (НТУ "ХПІ", 2017)
У статті розглянуті теоретичні питання процесу формування системи контролінгу на підприємствах. Наведено статистичні дані реалізованої продук- ції промисловості України. Проведено порівняльний аналіз фінансово-господарського стану промислових підприємств. Виявлено тенденції, диспропорції та нерівномірність розвитку, визначені індикатори стану, які використовують для побудови інтегральних індексів, що характеризують рівень розвитку, конкурентоспроможності Встановлені риси та особливості інноваційної активності промислових підприємств, на нашу думку, впливатимуть на формування цілей та сценарій запровадження контролінгу та фінансово-економічної безпеки підприємств.

The article deals with theoretical questions of the process of formation of a control system at enterprises. The statistical data of the realized industrial production of Ukraine are presented. A comparative analysis of the financial and economic condition of industrial enterprises was carried out. The activity of innovatively active enterprises of Ukraine is analyzed. The main constraints on the formation of a controlling system are described. The trends, disproportions and unevenness of development are revealed, state indicators are used that are used to construct integral indices characterizing the level of development, competitiveness. The established features and peculiarities of innovation activity of industrial enterprises, in our opinion, will influence the formation of goals and the scenario of the introduction of control.conomic security of enterprises.
Trends in the formation of a controlling system at engineering enterprises of Ukraine
Keywords: промисловість; інновації; стан фінансовий; industry; innovation; financial condition